2020
DOI: 10.1186/s12935-020-01617-w
|View full text |Cite
|
Sign up to set email alerts
|

Circ0120816 acts as an oncogene of esophageal squamous cell carcinoma by inhibiting miR-1305 and releasing TXNRD1

Abstract: Background Circular RNAs (circRNAs) have been discovered to participate in the carcinogenesis of multiple cancers. However, the role of circRNAs in esophageal squamous cell carcinoma (ESCC) progression is yet to be properly understood. This research aimed to investigate and understand the mechanism used by circRNAs to regulate ESCC progression. Methods Bioinformatics analysis was first performed to screen dysregulated circRNAs and di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 75 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…For example, miR-1305 is related to cell metastasis in bladder cancer [ 10 ]. Besides, miR-1305 takes part in regulating cell adhesion and cell apoptosis in esophageal squamous cell carcinoma cells [ 11 ]. Moreover, miR-1305 acts as a vital regulator in hepatocellular carcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-1305 is related to cell metastasis in bladder cancer [ 10 ]. Besides, miR-1305 takes part in regulating cell adhesion and cell apoptosis in esophageal squamous cell carcinoma cells [ 11 ]. Moreover, miR-1305 acts as a vital regulator in hepatocellular carcinoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, Li et al . disclosed that TXNRD1 was overexpressed in ESCC tissues, and miR-1305 exerted a tumor-suppressive function in ESCC cells via repressing TXNRD1 [ 23 ]. Consistently, we found that TXNRD1 level was enhanced in ESCC, and TXNRD1 upregulation abated the repressive function of miR-490-5p by increasing cell growth, monbility and glycolysis and decreasing apoptosis in ESCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that circFNDC3B may interact with miR-490-5p, however, whether circFNDC3B can act as a sponge molecule for miR-490-5p is unclear. Thioredoxin reductase 1 (TXNRD1) acts as a tumor promoter in ESCC [ 23 ]. TXNRD1 has been predicted to be a downstream target of miR-490-5p, but whether miR-490-5p can target TXNRD1 to affect ESCC remains poorly documented.…”
Section: Introductionmentioning
confidence: 99%
“…It is the sixth most common malignant tumor in the world, with high mortality, difficult treatment and poor surgical prognosis. More and more reports have shown that circRNAs, as an endogenous noncoding RNA, play an indispensable role numerous cancers, such as breast cancer [28], ovarian cancer [29], esophageal cancer [30], and liver cancer [31]. However, circ_0090049 has been relatively poorly studied in cancer.…”
Section: Discussionmentioning
confidence: 99%